The determinants of foreign direct investment in Central Asian region: A case study of Tajikistan, Kazakhstan, Kyrgyzstan, Turkmenistan and Uzbekistan (A quantitative analysis using GMM) - Ashurov, Sharofiddin; Othman, Anwar Hasan Abdullah; Rosman, Romzie; Haron, Razali ("Redaktsiya zhurnala Voprosy Ekonomiki" (Moscow, Russia, 2020)
Foreign direct investment (FDI) is viewed as one of the most crucial forms of capital inflows and significant drivers of economic growth in numerous countries. In particular, developing countries, emerging economies and countries engaged in the process of development have recognized the crucial importance of FDI as a critical contributor to their economic progress and increasing economic opportunities. The following research investigated and identified the determinants of FDI in the Central Asian countries, specifically Tajikistan, Kazakhstan, Kyrgyzstan, Turkmenistan and Uzbekistan, between 2000 and 2017. The methodology employed in the first part included comparative analysis of the foreign investment trends and gross domestic product (GDP), as well as an endogenous growth model. The result showed that five variables are robustly significant of FDI determinants: FDI (previous year), GDP, labor force, trade openness and tax. Additionally, this paper demonstrates that among the most significant FDI contributors are China, Russia and Japan as well as European countries because of the economic opportunities available; however, the USA is considered by Central Asian countries to offer the most opportunities for security control considerations rather than economic opportunities. Furthermore, the results suggest that the authorities in the Central Asia region should enhance the stability of their economic growth, labor force, trade openness and tax regulations to attract more FDI to the region.